(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The aim of this research paper is to investigate the impact of motivation factors on the performance of employees in the corporate sector. The study takes into account three factors of motivation, namely Workplace Environment, Co-Worker Relationships and Work-Life Balance and tested its impact on the job performance of the employees. The study reviewed number of past researches and then establishes hypotheses for the present research. The sample size of the study is 314 and the population is primarily the HR professionals and employees of different organizations of NCR, India. The data is analyzed through statistical techniques i.e. regression analysis in order to determine the impact of independent variables on the dependent variable. The results of the data analysis conclude that all of these factors i.e. Workplace environment, Co-Worker Relationships and Work-Life Balance has positive and significant impact on the employee performance. The study also suggests that Co-Worker Relationships was the most significant factor amongst all which impacts most the employee performance. The study concludes that organizations should introduce appropriate motivation strategies for their employees which fulfill all their needs and wants, so that employee can perform better for the organization.